A randomized controlled trial comparing Pentazocine and Chamomilla recutita for labor pain relief. Issue 1 (February 2016) - Zafar, Shamsa; Najam, Yawar; Arif, Zaeema; Hafeez, Assad
Abstract : Background: Traditional birth attendants in Pakistan sometimes use a homeopathic remedy, Chamomilla for labor pain relief. Our study compares this homeopathic remedy for pain relief in labor with a commonly used parenteral analgesic in a hospital setting. No systematic study has been conducted previously to study the effect of chamomile, which may be affordable and available in community settings. Methods: A double blind randomized controlled trial was carried out at Islamic International Medical College Trust. Ninety-nine normal pregnant women were randomly assigned into three groups. Each group received one of the three trial drugs; Chamomile, Pentazocine or placebo. The efficacy of labor analgesia was assessed by using Visual Analogue Scale (VAS) for pain intensity. Indicators of maternal and child health were recorded as were adverse effects of the drugs. Results: Mean pain scores in the three groups were calculated and compared. The difference in mean VAS scores in Pentazocine and Chamomilla recutita group as compared with placebo was not statistically significant. No significant adverse effects were noticed in any group except slight headache and dizziness in three parturients in Pentazocine group. Conclusion: Neither Pentazocine, or Chamomilla recutita offer substantial analgesia during labor.